The role of the subcortical structures in subthreshold depression: evidence from static and dynamic functional connectivity - Siying Zhang; Lijun Ma; Jiangzhou Sun; Yujie Chen; Yuanyun He; Qiutong Long; Bingqing Jiao; Huiyuan Huang; Lei Mo; Jiabao Lin (Brain Structure and Function, 2026)

Ultrastructural response of the retinal cells and neurovascular unit to neuroinflammation induced by lipopolysaccharide - Bilin Rao; Xiaotian Wu; Xiaoqing Liu; Fenglan Wang; Fang He; Xin Lin; Guiyu Guan; Xiaoqian Lai; Jun Zhang (Brain Structure and Function, 2026)

Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Consistent neural evidence to support novelty and appropriateness processing for creative thinking: a coordinated meta-analysis using activation likelihood estimation - Jiabao Lin; Yuanyun He; Siying Zhang; Lei Mo; Changyi Kuang; Yajue Chen (Brain Structure and Function, 2026)

Distinct cellular localization of α- synuclein and β-synuclein in the chick retina - Fang He; Lin Liu; Shaoxuan Wang; Xin Lin; Guiyu Guan; Xiaoqian Lai; Xi Yu; Xiaotian Wu; Zhihao Shen; Bilin Rao; Mei-Ling Gao; Xuejiao Chen; et al. (Brain Structure and Function, 2025)

Beyond tractography in brain connectivity mapping with dMRI morphometry and functional networks - Jui-To Wang; Ching-Po Lin; Huei-Min Liu; Carlo Pierpaoli; Chun-Yi Zac Lo (Brain Structure and Function, 2025)
Traditional brain connectivity studies have focused mainly on structural connectivity, often relying on tractography with diffusion MRI (dMRI) to reconstruct white matter pathways. In parallel, studies of functional connectivity have examined correlations in brain activity using fMRI. However, emerging methodologies are advancing our understanding of brain networks. Here we explore advanced connectivity approaches beyond conventional tractography, focusing on dMRI morphometry and the integration of structural and functional connectivity analysis. dMRI morphometry enables quantitative assessment of white matter pathway volumes through statistical comparison with normative populations, while functional connectivity reveals network organization that is not restricted to direct anatomical connections. More recently, approaches that combine diffusion tensor imaging (DTI) with functional correlation tensor (FCT) analysis have been introduced, and these complementary methods provide new perspectives into brain structure–function relationships. Together, such approaches have important implications for neurodevelopmental and neurological disorders as well as brain plasticity. The integration of these methods with artificial intelligence techniques have the potential to support both basic neuroscience research and clinical applications.

Developmental expression of α- and β- synuclein in the mouse retina - Wenhui Zhong; Zhongqun Chen; Shaoxuan Wang; Jun Cao; Xin Lin; Xiaoqian Lai; Bilin Rao; Jun Zhang (Brain Structure and Function, 2025)

Classifying athletes and non-athletes by differences in spontaneous brain activity: a machine learning and fMRI study - Lei Peng; Lin Xu; Zheyuan Zhang; Zexuan Wang; Xiao Zhong; Letong Wang; Ziyi Peng; Ruiping Xu; Yongcong Shao (Brain Structure and Function, 2025)

Understanding tractography in edematous brain regions: challenges and solutions - Shin Tai Chong; Joseph Yuan-Mou Yang; Ching-Po Lin (Brain Structure and Function, 2025)

Decreases in frequency-dependent intrinsic activity of the default mode network are associated with depression and cognition in patients with postacute sequelae of SARS-CoV-2 infection - Yao Wang; Ziwei Yang; Xiumei Zheng; Xiao Liang; Lin Wu; Chengsi Wu; Jiankun Dai; Yuan Cao; Xianjun Zeng; Meng Li; Fuqing Zhou (Brain Structure and Function, 2025)

ds-FCRN: three-dimensional dual-stream fully convolutional residual networks and transformer-based global–local feature learning for brain age prediction - Yutong Wu; Chen Zhang; Xiangge Ma; Xinyu Zhu; Lan Lin; Miao Tian (Brain Structure and Function, 2025)

Microglia heterogeneity during neuroinflammation and neurodegeneration in the mouse retina - Bilin Rao; Xiaoqing Liu; Jiayi Xiao; Xiaotian Wu; Fang He; Qingwen Yang; Wenna Zhao; Xin Lin; Jun Zhang (Brain Structure and Function, 2024)

Cell-specific localization of β-synuclein in the mouse retina - Wenhui Zhong; Qingwen Yang; Fenglan Wang; Xin Lin; Zhongqun Chen; Jing Xue; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Jun Zhang (Brain Structure and Function, 2024)

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

Distribution and synaptic organization of substance P-like immunoreactive neurons in the mouse retina - Fenglan Wang; Wenhui Zhong; Qingwen Yang; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Xin Lin; Jun Zhang (Brain Structure and Function, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Coexistence of the social semantic effect and non-semantic effect in the default mode network - Guangyao Zhang; Jinyi Hung; Nan Lin (Brain Structure and Function, 2023)

Diffeomorphic registration for retinotopic maps of multiple visual regions - Yanshuai Tu; Xin Li; Zhong-Lin Lu; Yalin Wang (Brain Structure and Function, 2022)

The impact of Alzheimer's disease susceptibility loci on lateral ventricular surface morphology in older adults - Shan Li; Na An; Nan Chen; Yin Wang; Lin Yang; Yalin Wang; Zhijun Yao; Bin Hu (Brain Structure and Function, 2022)

An extended Human Connectome Project multimodal parcellation atlas of the human cortex and subcortical areas - Chu-Chung Huang; Edmund T. Rolls; Jianfeng Feng; Ching-Po Lin (Brain Structure and Function, 2022)

Postnatal development of BAG3 expression in mouse cerebral cortex and hippocampus - Xinlu Li; Geng Lin; Tongtong Liu; Ning Zhao; He Xu; Huaqin Wang; Wei Zheng (Brain Structure and Function, 2021)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Dissociable plasticity of visual-motor system in functional specialization and flexibility in expert table tennis players - Dazhi Yin; Xuefei Wang; Xiaoyou Zhang; Qiurong Yu; Yu Wei; Qing Cai; Mingxia Fan; Lin Li (Brain Structure and Function, 2021)

Neuroplastin expression is essential for hearing and hair cell PMCA expression - Xiao Lin; Michael G. K. Brunk; Pingan Yuanxiang; Andrew W. Curran; Enqi Zhang; Franziska Stöber; Jürgen Goldschmidt; Eckart D. Gundelfinger; Maike Vollmer; Max F. K. Happel; Rodrigo Herrera-Molina; Dirk Montag (Brain Structure and Function, 2021)
Hearing deficits impact on the communication with the external world and severely compromise perception of the surrounding. Deafness can be caused by particular mutations in the neuroplastin ( Nptn ) gene, which encodes a transmembrane recognition molecule of the immunoglobulin (Ig) superfamily and plasma membrane Calcium ATPase (PMCA) accessory subunit. This study investigates whether the complete absence of neuroplastin or the loss of neuroplastin in the adult after normal development lead to hearing impairment in mice analyzed by behavioral, electrophysiological, and in vivo imaging measurements. Auditory brainstem recordings from adult neuroplastin-deficient mice ( Nptn −/− ) show that these mice are deaf. With age, hair cells and spiral ganglion cells degenerate in Nptn −/− mice. Adult Nptn −/− mice fail to behaviorally respond to white noise and show reduced baseline blood flow in the auditory cortex (AC) as revealed by single-photon emission computed tomography (SPECT). In adult Nptn −/− mice, tone-evoked cortical activity was not detectable within the primary auditory field (A1) of the AC, although we observed non-persistent tone-like evoked activities in electrophysiological recordings of some young Nptn −/− mice. Conditional ablation of neuroplastin in Nptn lox/loxEmx1Cre mice reveals that behavioral responses to simple tones or white noise do not require neuroplastin expression by central glutamatergic neurons. Loss of neuroplastin from hair cells in adult Nptn Δlox/loxPrCreERT mice after normal development is correlated with increased hearing thresholds and only high prepulse intensities result in effective prepulse inhibition (PPI) of the startle response. Furthermore, we show that neuroplastin is required for the expression of PMCA 2 in outer hair cells. This suggests that altered Ca 2+ homeostasis underlies the observed hearing impairments and leads to hair cell degeneration. Our results underline the importance of neuroplastin for the development and the maintenance of the auditory system.

Integrated and segregated frequency architecture of the human brain network - Junji Ma; Ying Lin; Chuanlin Hu; Jinbo Zhang; Yangyang Yi; Zhengjia Dai (Brain Structure and Function, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

A generic brain connectome map linked to different types of everyday decision-making in old age - Brian Rooks; Mia Anthony; Quanjing Chen; Ying Lin; Timothy Baran; Zhengwu Zhang; Peter A. Lichtenberg; Feng Lin (Brain Structure and Function, 2020)

Dissociating the neural correlates of the sociality and plausibility effects in simple conceptual combination - Nan Lin; Yangwen Xu; Huichao Yang; Guangyao Zhang; Meimei Zhang; Shaonan Wang; Huimin Hua; Xingshan Li (Brain Structure and Function, 2020)

Rostral intralaminar thalamic deep brain stimulation ameliorates memory deficits and dendritic regression in β-amyloid-infused rats - Sheng-Tzung Tsai; Shin-Yuan Chen; Shinn-Zong Lin; Guo-Fang Tseng (Brain Structure and Function, 2020)

Laminar specificity of oscillatory coherence in the auditory cortex - Francisco García-Rosales; Dennis Röhrig; Kristin Weineck; Mira Röhm; Yi-Hsuan Lin; Yuranny Cabral-Calderin; Manfred Kössl; Julio C. Hechavarria (Brain Structure and Function, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Electrotonic signal processing in AII amacrine cells: compartmental models and passive membrane properties for a gap junction-coupled retinal neuron - Bas-Jan Zandt; Margaret Lin Veruki; Espen Hartveit (Brain Structure and Function, 2018)

AMPA receptors at ribbon synapses in the mammalian retina: kinetic models and molecular identity - Espen Hartveit; Bas-Jan Zandt; Eirik Madsen; Áurea Castilho; Svein Harald Mørkve; Margaret Lin Veruki (Brain Structure and Function, 2018)

Brain structural concomitants of resting state heart rate variability in the young and old: evidence from two independent samples - Hyun Joo Yoo; Julian F. Thayer; Steven Greening; Tae-Ho Lee; Allison Ponzio; Jungwon Min; Michiko Sakaki; Lin Nga; Mara Mather; Julian Koenig (Brain Structure and Function, 2018)

Co-altered functional networks and brain structure in unmedicated patients with bipolar and major depressive disorders - Hao He; Jing Sui; Yuhui Du; Qingbao Yu; Dongdong Lin; Wayne C. Drevets; Jonathan B. Savitz; Jian Yang; Teresa A. Victor; Vince D. Calhoun (Brain Structure and Function, 2017)

Formation of GABAA receptor complexes containing α1 and α5 subunits is paralleling a multiple T-maze learning task in mice - Maryam Ghafari; Soheil Keihan Falsafi; Edit Szodorai; Eun-Jung Kim; Lin Li; Harald Höger; Johannes Berger; Karoline Fuchs; Werner Sieghart; Gert Lubec (Brain Structure and Function, 2017)

AII amacrine cells: quantitative reconstruction and morphometric analysis of electrophysiologically identified cells in live rat retinal slices imaged with multi-photon excitation microscopy - Bas-Jan Zandt; Jian Hao Liu; Margaret Lin Veruki; Espen Hartveit (Brain Structure and Function, 2017)

Hippocampal size is related to short-term true and false memory, and right fusiform size is related to long-term true and false memory - Bi Zhu; Chuansheng Chen; Elizabeth F. Loftus; Qinghua He; Xuemei Lei; Qi Dong; Chongde Lin (Brain Structure and Function, 2016)

Interactions of early adversity with stress-related gene polymorphisms impact regional brain structure in females - Arpana Gupta; Jennifer Labus; Lisa A. Kilpatrick; Mariam Bonyadi; Cody Ashe-McNalley; Nuwanthi Heendeniya; Sylvie Bradesi; Lin Chang; Emeran A. Mayer (Brain Structure and Function, 2016)

Cortical thickness and surface area in neonates at high risk for schizophrenia - Gang Li; Li Wang; Feng Shi; Amanda E. Lyall; Mihye Ahn; Ziwen Peng; Hongtu Zhu; Weili Lin; John H. Gilmore; Dinggang Shen (Brain Structure and Function, 2016)

Development of human brain cortical network architecture during infancy - Wei Gao; Sarael Alcauter; J. Keith Smith; John H. Gilmore; Weili Lin (Brain Structure and Function, 2015)

Dorsal hippocampal brain receptor complexes linked to the protein synthesis-dependent late phase (LTP) in the rat - Lin Li; Han Wang; Maryam Ghafari; Gunyong An; Volker Korz; Gert Lubec (Brain Structure and Function, 2015)

Gray and white matter structures in the midcingulate cortex region contribute to body mass index in Chinese young adults - Qinghua He; Chuansheng Chen; Qi Dong; Gui Xue; Chunhui Chen; Zhong-Lin Lu; Antoine Bechara (Brain Structure and Function, 2015)

Orexins (hypocretins) contribute to fear and avoidance in rats exposed to a single episode of footshocks - Xiaoyu Chen; Huiying Wang; Zhang Lin; Sa Li; Yonghui Li; Hugo T. Bergen; Maria E. Vrontakis; Gilbert J. Kirouac (Brain Structure and Function, 2014)

Medullo-ponto-cerebellar white matter degeneration altered brain network organization and cortical morphology in multiple system atrophy - Chia-Feng Lu; Po-Shan Wang; Yuan-Lin Lao; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Brain Structure and Function, 2014)

More insights into early brain development through statistical analyses of eigen-structural elements of diffusion tensor imaging using multivariate adaptive regression splines - Yasheng Chen; Hongtu Zhu; Hongyu An; Diane Armao; Dinggang Shen; John H. Gilmore; Weili Lin (Brain Structure and Function, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)

Neuroanatomical consequences of very preterm birth in middle childhood - Ilyse D. Lax; Emma G. Duerden; Sarah Y. Lin; M. Mallar Chakravarty; Elizabeth J. Donner; Jason P. Lerch; Margot J. Taylor (Brain Structure and Function, 2013)